Adolescents’ Attitudes toward Taxes: Case of Lithuania - Mikuličiūtė, Vita; Rakickienė, Lauryna; Valickas, Gintautas; Vanagaitė, Kristina (Socialinė teorija, empirija, politika ir praktika, 2025)
Objectives. Considering that adolescents are future tax payers, it is unfortunate that we know virtually nothing about their attitudes toward taxes. The goal of our research is to analyze the effects of sociodemographic characteristics such as age, gender, parental education and place of residence on adolescents’ attitudes toward taxes. Sample and settings. The participants were 1246 adolescents aged 11 to 18 (M = 14.30, SD = 1.98); 57 percent of the participants were female. Adolescents completed a questionnaire on attitudes toward taxes, whereas their parents provided sociodemographic information. Scale of Adolescents’ Attitudes toward Taxes, consisting of 12 items falling into one of four interrelated attitude dimensions (Perceived fairness of taxation, Perceived inevitability of tax paying, Readiness to report tax evasion, and Readiness to pay taxes) has been specifically created for the purposes of this research. Statistical analysis. Correlation analysis, Independent sample t-test, ANOVA test, Exploratory and Confirmatory factor analysis were used in the framework of this research. Results. Age emerged as the only sociodemographic characteristic related to the general attitude toward taxes in adolescence: attitudes toward taxes tend to become more negative with age. The remaining three sociodemographic characteristics (gender, parental education, and the place of residence) were related only to some of the attitude dimensions with small effect sizes. Limitations. Generalization of the results to more diverse societies is limited because of the socioeconomic history of Lithuania.
Keywords: attitudes toward taxes; adolescents; sociodemographic characteristics; socialization